INTEGRATED ENGINEERING SYSTEMS THINKING: CROSS-DOMAIN METHODOLOGIES FOR COMPLEX TECHNOLOGICAL CHALLENGES - Chevi Herli Sumerli; Sota Yamamoto; Sakura Suzuki (Journal of Moeslim Research Technik, 2026)
The complexity of modern technological systems requires a shift from isolated engineering disciplines to more integrated approaches. Traditional engineering methodologies often fail to address the interconnected challenges presented by multi-disciplinary problems. Systems thinking, particularly when applied across domains, offers a more holistic framework that can optimize technological solutions by considering the interrelationships between various system components. This research investigates the application of integrated engineering systems thinking to complex technological challenges, emphasizing the value of cross-domain methodologies in improving efficiency, sustainability, and innovation. The study aims to develop a comprehensive framework for applying systems thinking across different engineering domains and to evaluate its effectiveness in real-world scenarios. A mixed-methods approach was employed, combining case studies from diverse sectors such as energy, manufacturing, and infrastructure, with data collected through interviews, surveys, and performance metrics. The findings reveal significant improvements in cost reduction, efficiency enhancement, and sustainability outcomes in organizations employing cross-domain methodologies. The research concludes that integrated engineering systems thinking provides a robust framework for solving complex technological problems, driving both operational performance and sustainable outcomes. Future studies should explore the long-term impacts and institutionalization of cross-domain collaboration in engineering practice.